Working with unaccompanied asylum-seeking young people: cultural considerations and acceptability of a cognitive behavioural group approach. (9th January 2019) - King, Dorothy; Said, Glorianne
Abstract: This paper outlines a psychological skills group for unaccompanied asylum-seeking young people with a focus on cultural adaptations in the context of a UK mental health service. Unaccompanied asylum-seeking young people have typically experienced multiple losses, traumatic experiences, significant disruption and psychosocial stressors. These experiences occur during a key developmental period and outside of the context of a supportive family environment. Mental health difficulties are estimated to be present in 41–69% of this population. Prevalence rates are higher than among children seeking asylum with their families or children who are not from refugee or asylum-seeking backgrounds. Cognitive behavioural approaches were considered to be applicable and useful when working with this client group. Group approaches may offer unique benefits for this population through peer support and normalization. The group described was planned around three key themes: physical health needs, emotional wellbeing and resilience-building. A number of adaptations were made to meet the needs of this population which included engagement, considering physical health needs, sleep, language needs, issues related to power, race and status, and thinking about the needs of the group as young people. Attendance ratings, session rating scale outcomes, preliminary effectiveness data and qualitative feedback from young people identified that this is an acceptable approach for these young people. Unaccompanied asylum-seeking young people require a broad package of care; however, making adaptations to routine practice allowed access to evidence-based interventions to support mental health and wellbeing.